2012
DOI: 10.1016/j.acvd.2012.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone-to-renin ratio for diagnosing aldosterone-producing adenoma: A multicentre study

Abstract: The proposed cut-off value of 32 ng/ng for ARR (minimum renin value set at 5 ng/L) in one of two determinations had 100% sensitivity and 72% specificity with 20% positive and 100% negative predictive values for diagnosing APA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 32 publications
3
12
2
Order By: Relevance
“…In the remaining three patients, the diagnosis of PA was not confirmed either due to an unaccounted ACTH surge or due to a false-positive ARR increasing the population requiring unnecessary confirmatory testing to ascertain the diagnosis. The sensitivity and specificity of basal ARR were found to be 18 and 98% respectively, considerably different from those published so far (16,70,87). These findings suggest that the use of basal ARR alone permits the detection of more advanced cases of PA leaving milder forms undiagnosed.…”
Section: Prevalence Of Pa In Hypertension and Pre-hypertensioncontrasting
confidence: 54%
“…In the remaining three patients, the diagnosis of PA was not confirmed either due to an unaccounted ACTH surge or due to a false-positive ARR increasing the population requiring unnecessary confirmatory testing to ascertain the diagnosis. The sensitivity and specificity of basal ARR were found to be 18 and 98% respectively, considerably different from those published so far (16,70,87). These findings suggest that the use of basal ARR alone permits the detection of more advanced cases of PA leaving milder forms undiagnosed.…”
Section: Prevalence Of Pa In Hypertension and Pre-hypertensioncontrasting
confidence: 54%
“…However, the criteria used to select patients met current recommendations and the main characteristics of our study population were similar to those usually reported in the literature [9]. In our study, the true disease status was based on an ARR > 32 ng/L after ≥ 1 hour in the reclined position or after 1 hour supine (with a plasma aldosterone value > 160 ng/L) [17]. The ARR based on the measurement of active renin is a valuable alternative to plasma renin activity [20].…”
Section: Discussionmentioning
confidence: 91%
“…We recorded factors that are clearly linked to the risk of primary aldosteronism [10,17] and discarded those that are still debated in the literature. Accordingly, the following data were collected:…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the introduction of direct renin assays in the clinical arena, several studies have examined ARR calculated with PRC [22][23][24][25][26][27][28] in patients with essential hypertension, but only in three of these comparing ARRD and ARRP [22,24,25]. However, all these investigations were carried out while patients were off treatment with antihypertensive agents, whereas we elected, on purpose, to perform our study while the majority of our patients were on their usual antihypertensive medications to assess how these drugs affect the specificity of ARRP and ARRD.…”
Section: Discussionmentioning
confidence: 99%